Evaluating Dietary Acidifiers as Alternatives to Conventional Feed-Based Antibiotics in Nursery Pig Diets - Payton L. Dahmer; Cassandra K. Jones (Kansas Agricultural Experiment Station Research Reports, 2021)
A total of 360 weanling pigs (200 × 400, DNA; initially 21.4 ± 0.23 lb BW) were used in a 21-d experiment with 6 pigs/pen, 10 replicate pens/treatment, and 2 separate nursery rooms, each with 30 pens. Pigs were weighed and allotted to pens based on BW in a completely randomized block design to one of six treatment diets: 1) negative control (no organic acids or antibiotics) and the control with 2) 0.25% acidifier A; 3) 0.3% acidifier B; 4) 0.5% acidifier C); 5) 50 g/ton carbadox; and 6) 400 g/ton chlortetracycline (CTC). Upon weaning, a common diet with no antibiotics or additives was fed for 21 d (Phases 1 and 2; days −21 to 0), followed by a 21-d experimental period (Phase 3; days 0 to 21) where treatment diets were fed. Pigs and feeders were individually weighed on a weekly basis to calculate ADG, ADFI, and F/G. Data were analyzed using the GLIMMIX procedure of SAS (v. 9.4, SAS Inst., Cary, NC) with pen as the experimental unit, treatment as a fixed effect, and room as a random effect. Dietary treatment had a significant impact (P<0.05) on ADG, ADFI, and G:F each week and for the overall experimental period (days 0 to 21). Specifically, from days 0 to 7, pigs fed CTC had increased (P= 0.001) ADG compared with those fed acidifier B, acidifier C, and carbadox, whereas pigs fed the negative control and acidifier A diets were intermediate. Additionally, pigs fed the CTC diet had improved (P= 0.0002) ADFI when compared with all other treatments. From days 7 to 14 and days 14 to 21, pigs fed the carbadox diet had decreased (P<0.0001) ADG compared with all other treatments. During the overall period (days 0 to 21), pigs fed diets containing carbadox had reduced ADG and ADFI (P<0.0001), whereas pigs fed CTC had improved (P<0.0001) ADG compared with all other treatments. Additionally, fecal consistency, and fecal microbial populations were analyzed on a subset of pigs (n= 5 pigs/treatment). Treatment also significantly impacted (P= 0.0005) fecal score but did not affect (P= 0.59) fecal microbial growth from days 0 to 21. In summary, CTC continues to be a valuable additive to improve performance in the nursery. Further investigation surrounding the efficacy of dietary acidifiers as antibiotic alternatives is warranted given inconclusive evidence in this study.
Keywords: nursery pig; acidifiers; growth performance; fecal microbiota